Design and tests of an efficient search algorithm for accurate linear valuation systems* - SHIH, MICHAEL S.H.; SUNDER, SHYAM (Contemporary Accounting Research, 1987)
A valuation system partitions the set of goods to be valued into multiple disjoint subsets and the current value of the goods is estimated via price indexes covering these subsets. Efficient valuation systems yield a relatively small economy‐wide average of mean squared errors with respect to the true total current cost of the goods. Several algorithms have been designed to search for efficient valuation systems. These algorithms, however, do not take advantage of the information contained in the characteristic parameters of the goods to be valued. We present the design and test of a search algorithm that is substantially more efficient than those in the literature. The relative efficiency of the algorithm is gained through the use of information contained in the weights, the expected values, and the variance‐covariance structure of the price changes of the goods. Résumé. Un système d'évaluation subdivise l'ensemble des biens à être évalués en plusieurs sous‐ensembles disjoints et la valeur actuelle des biens est estimée grâce à des indices de prix couvrant ces sous‐ensembles. Des systèmes d'évaluation efficaces produisent, pour l'ensemble de l'économie, une moyenne relativement faible des erreurs moyennes au carré, par rapport au coût actuel réel total des biens. Plusieurs algorithmes ont été conçus pour découvrir des systèmes d'évaluation efficaces. Toutefois, ces algorithmes n'intègrent pas l'information que renferment les paramètres caractérisant les biens à évaluer. Nous présentons la conception et le test d'un algorithme de recherche qui s'avère considérablement plus efficace que ceux mentionnés dans les recherches antérieures. L'efficacité relative de cet algorithme est obtenue grâce à l'intégration de l'information contenue dans les pondérations, les valeurs espérées et la structure de variance‐covariance des fluctuations de prix des biens.